Engineering the electrochemical performance of CoWO4 composites of MXene by transitional metal ion doping for high energy density supercapacitors - Vigneshwaran J.; Prasankumar T.; Ansari M.N.M.; Lim H.-T.; Yuliarto B.; Jose S.P. (Springer, 2025)
This investigation presents a straightforward synthesis method for a CoWO4@Ti3C2Tx composite doped with transitional metals, serving as innovative cathode materials for supercapacitors. The study delves into the structural, morphological, and electrochemical attributes of these composites, revealing that the Ni-doped variant outperforms its Zn/Cu-doped counterparts in capacitive capabilities. Specifically, the Ni-doped MXene composite within the CoWO4 electrode exhibits a remarkable specific capacitance of 630Fg?1 at a current density of 1Ag?1, showcasing superior performance. Moreover, this composite demonstrates notable cycling stability, retaining 92% of its initial capacitance over 10000 cycles. To further explore practical applications, an asymmetric supercapacitor coin cell (CR2032) was assembled, when displays a high voltage window of 1.6V in a 1MH2SO4 electrolyte, yielding a specific capacitance of 248Fg?1 at 1Ag?1. Notably, the device achieves an energy density of 63.8Whkg?1 at a power density of 422Wkg?1, accompanied by an impressive 95.6% coulombic efficiency. The practical viability of the fabricated supercapacitor prototype is underscored by its ability to power a green light-emitting diode within 10min of a 10-s charge. This highlights the potential of the composite electrode material for constructing high-performance supercapacitors, assessed morphologically and benchmarked against other metal-doped samples. ? The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.